V2V Communication Using LiFi - Adhithyan S; Anupama Asokan; Maneesha Mohan; Athira Chandran (International Journal of Optical Innovations & Research, 2024)
The global status report on road safety launched by the World Health Organization (WHO) highlights that the number of annual road traffic deaths has reached 1.35 million. In the USA over 37,000 people die in road crashes each year and an additional 2.35 are injured or disabled. The direct impact of road accidents is loss of life as well as damage to vehicles and property. Accidents might happen due to careless driving, negligence of the driver, over speeding etc. According to research, efficient communication between vehicles and warning systems put in place can reduce or prevent 80% of these crashes. Based on these reasons V2V solutions were expected to provide efficient vehicle communication mechanisms enhancing road safety. V2V has the goal to facilitate efficient and reliable communication without predominantly relying on a global system for mobile communication (GSM) network. The main feature of V2V is that it does not rely on third party networks like cellular networks to communicate. V2V can be used to improve traffic conditions, reduce road accidents and increase the safety of passengers. This paper discusses solutions and adaptations to make LiFi viable in such scenarios, potentially enhancing communication, connectivity, and safety within vehicles. In the proposed project we implement features like sudden brake alert, collision alarms and blind spot warnings to prevent accidents due to vehicles coming in close proximity to another due to carelessness or distraction.
Keywords: Arduino; ESD; GSM; LIFI; V2V; piezoelectric